Redox Epiphospholipidome in Programmed Cell Death Signaling: Catalytic Mechanisms and Regulation - Kagan, Valerian E.; Tyurina, Yulia Y.; Vlasova, Irina I.; Kapralov, Alexander A.; Amoscato, Andrew A.; Anthonymuthu, Tamil S.; Tyurin, Vladimir A.; Shrivastava, Indira H.; Cinemre, Fatma B.; Lamade, Andrew; Epperly, Michael W.; Greenberger, Joel S.; et al. (Frontiers in Endocrinology, 2021)
A huge diversification of phospholipids, forming the aqueous interfaces of all biomembranes, cannot be accommodated within a simple concept of their role as membrane building blocks. Indeed, a number of signaling functions of (phospho)lipid molecules has been discovered. Among these signaling lipids, a particular group of oxygenated polyunsaturated fatty acids (PUFA), so called lipid mediators, has been thoroughly investigated over several decades. This group includes oxygenated octadecanoids, eicosanoids and docosanoids and includes several hundreds of individual species. Oxygenation of PUFA can occur when they are esterified into major classes of phospholipids. Initially, these events have been associated with non-specific oxidative injury of biomembranes. An alternative concept is that these post-synthetically oxidatively modified phospholipids and their adducts with proteins are a part of a redox epiphospholipidome that represents a rich and versatile language for intra- and inter-cellular communications. The redox epiphospholipidome may include hundreds of thousands of individual molecular species acting as meaningful biological signals. This review describes the signaling role of oxygenated phospholipids in programs of regulated cell death. Although phospholipid peroxidation has been associated with almost all known cell death programs, we chose to discuss enzymatic pathways activated during apoptosis and ferroptosis and leading to peroxidation of two phospholipid classes, cardiolipins (CLs) and phosphatidylethanolamines (PEs). This is based on the available LC-MS identification and quantitative information on the respective peroxidation products of CLs and PEs. We focused on molecular mechanisms through which two proteins, a mitochondrial hemoprotein cytochrome c (cyt c), and non-heme Fe lipoxygenase (LOX), change their catalytic properties to fulfill new functions of generating oxygenated CL and PE species. Given the high selectivity and specificity of CL and PE peroxidation we argue that enzymatic reactions catalyzed by cyt c/CL complexes and 15-lipoxygenase/phosphatidylethanolamine binding protein 1 (15LOX/PEBP1) complexes dominate, at least during the initiation stage of peroxidation, in apoptotis and ferroptosis. We contrast cell-autonomous nature of CLox signaling in apoptosis correlating with its anti-inflammatory functions vs. non-cell-autonomous ferroptotic signaling facilitating pro-inflammatory (necro-inflammatory) responses. Finally, we propose that small molecule mechanism-based regulators of enzymatic phospholipid peroxidation may lead to highly specific anti-apoptotic and anti-ferroptotic therapeutic modalities.